PH monitoring system, temperature automation and clown fish feeding in aquarium using fuzzy logic method based on internet of things - Purnama Insany Gina; Somantri; Zulfa Oktaviani Siti; Sujjada Alun; Lucia Kharisma Ivana (BIO Web of Conferences)
Clown fish are marine ornamental fish that are in great demand because they have unique beauty and economical prices. Aquariums are used as a medium for keeping clown fish. However, clown fish are difficult so find on the market because clown fish care must pay attention to all aspects, including the condition of the fish. Fish food, water pH and water temperature. Overcoming this problem is by creating a pH monitoring system, temperature automation and fish feed in aquariums based on the Internet of Things (IoT). Implementation of this system can be controlled and monitored remotely via the website. Monitoring water pH uses a pH- 4502C sensor connected to the Node MCU and DS18B20 sensor to control water temperature. Water temperature automation uses the fuzzy logic method. When the water temperature is below 25℃ the heater will turn on to increase the water temperature to normal and after the temperature becomes normal the heater will turn off, while at temperatures above 28℃ the fan cooler will turn on and after the temperature becomes normal the fan cooler will turn off. Black box testing is used to test the monitoring system that has been designed and the test results show that this system has worked well, and usability testing has been carried out by 18 respondents, 87% agree with the system.